The Essence of Software Engineering: The SEMAT Kernel. - Jacobson, Ivar; Pan-Wei Ng; McMahon, Paul E.; Spence, Ian; Lidman, Svante (Communications of the ACM, 2012)
The article discusses a thinking framework that can be applied to software engineering based on an actionable kernel, a main component in computer operating systems. It states that development of the kernel was inspired by a prompt from the Software Engineering Methods and Theory (SEMAT), an initiative to redefine software engineering based on proven principles and best practices. The authors note that the kernel's benefits include providing a method of discussion and improvement regarding software-engineering methods, a foundation for defining practices for assessing software quality, and a way for engineers to track their progress. Other topics covered include software development methods, iterations, and practical applications of the kernel.